1982
DOI: 10.1093/ajcn/36.4.602
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle function in malnutrition

Abstract: Skeletal muscle function was studied in 10 malnourished patients with various gastrointestinal disorders and in 22 normal subjects. The function of the adductor pollicis muscle was assessed by electrical stimulation of the ulnar nerve. The objective parameters of muscle function measured were: 1) Force of contraction expressed as a percentage of the maximal force obtained with electrical stimulation at 10, 20, 30, 50 and 100 Hz. 2) Maximal relaxation rate expressed as percentage force loss/!10 ms. 3) Endurance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
115
0
6

Year Published

1983
1983
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(123 citation statements)
references
References 14 publications
1
115
0
6
Order By: Relevance
“…Whether there is a beneficial effect of DR on muscle function has been controversial to date, because whereas some studies have shown that DR improves muscle function (Marzetti, Lees, Wohlgemuth, & Leeuwenburgh, 2009; McKiernan et al., 2012), another showed it had the opposite effect (Lopes et al., 1982). Our results demonstrate that DR can improve slow‐twitch muscle fiber function, along with the maintenance of muscle fiber size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether there is a beneficial effect of DR on muscle function has been controversial to date, because whereas some studies have shown that DR improves muscle function (Marzetti, Lees, Wohlgemuth, & Leeuwenburgh, 2009; McKiernan et al., 2012), another showed it had the opposite effect (Lopes et al., 1982). Our results demonstrate that DR can improve slow‐twitch muscle fiber function, along with the maintenance of muscle fiber size.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, DR has only one principal negative effect: muscle weakness due to protein wasting (Lopes, Russell, Whitwell, & Jeejeebhoy, 1982; Thomas, 2007), which also represents a health problem in both elderly subjects and patients with kidney disease (Goodpaster et al., 2006; Workeneh & Mitch, 2010). Recently, a beneficial effect of dietary protein or amino acid supplementation on muscle weakness has been proposed (Paddon‐Jones & Rasmussen, 2009; Paddon‐Jones, Short, Campbell, Volpi, & Wolfe, 2008; Volpi, Kobayashi, Sheffield‐Moore, Mittendorfer, & Wolfe, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that skeletal muscle function seems to be sensitive indicator of nutritional status in patients (Lopes et al, 1982), as functional changes occurred before abnormalities in conventional indices of malnutrition were observed (Cristie & Hill, 1990;Russell et al, 1983). In patients with long-standing CD, currently in remission, we observed a signi®cantly reduced strength of the hamstring muscles (with a high percentage of type IIb ®bres), whereas the strength of the quadriceps muscles was preserved (Geerling et al, 1998a, b).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that handgrip strength (HGS) can be used as a nutritional assessment technique that is also sensitive in evaluating short-term changes in nutritional status (Lopes et al, 1982;Windsor and Hill, 1988;Webb et al, 1989;Ades et al, 2002;Humphreys et al, 2002). Muscle strength, measured by handgrip dynamometry, has been shown to be both sensitive and specific in predicting outcome in surgical patients (Klidjian et al, 1982;Hunt et al, 1985;Kalfarentzos et al, 1989;Webb et al, 1989;Pieterse et al, 2002;Bunout et al, 2004;Mahalakshmi et al, 2004), and cirrhotic patients (Á lvares-da-Silva and Da Silveira 2005), as well as being associated with higher long-term mortality (Newman et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A loss of body cellular mass causes an unequal decrease of muscle strength, which implies that a higher loss of functionality than a corresponding loss of skeletal muscle mass occurs (Vaz et al, 1996). These changes in muscle function such as contractility, relaxation rate and endurance may anticipate body composition changes and may help detect functional impairment at sub clinical levels (Lopes et al, 1982). HGS could offer several advantages as a nutritional screening method.…”
Section: Introductionmentioning
confidence: 99%